Pertumbuhan tanaman pulai darat (Alstonia angustiloba Miq.) dari empat populasi pada umur satu tahun di Wonogiri, Jawa Tengah - Mashudi; Hamdan Adma Adinugraha (Jurnal Penelitian Kehutanan Wallacea, 2014)
This experiment aims to identify the effects of population sources and parent trees on the growth of Alstonia angustiloba of one year old. This experiment was arranged in randomized complete block design. The research used two factors, i.e. population sources (Carita-Banten, Pendopo-Muara Enim, Lubuk Linggau-Musi Rawas and Solok- West Sumatera), and parent trees (43 parent trees). In this experiment, parent trees factor was nested in the population sources. The result showed that population sources and parent trees significantly affected the parameters measured, i.e. height and stem diameter. Pendopo and Carita were the best two populations in terms of height (1,612 m and 1,597 m, respectively) and stem diameter (2,567 cm and 2,686 cm, respectively). The best ten parent trees for height were parent trees number 13 (1.884 m), 16 (1.808 m), 17 (1.773 m), 8 (1.688 m), 6 (1.684 m), 15 (1.682 m), 20 (1.677 m), 36 (1.652 m), 18 (1.652 m) and 14 (1.630 m). The best ten of parent trees for stem diameter were parent trees number 16 (3.171 cm), 7 (3.116 cm), 13 (3.105 cm), 8 (3.027 cm), 36 (3.022 cm), 27 (2.974 cm), 15 (2.925 cm), 30 (2.787 cm), 6 (2.766 cm) and 18 (2.757 cm).